Gender gaps in ownership of nonagricultural enterprises in Georgia, Mongolia, and the Philippines - Hema Swaminathan; Arturo Martinez; Kaushal Joshi; Mildred Addawe; Christian Flora Mae Soco; Remedios Baes-Espineda (Asian Development Bank (ADB), 2023)
Using unique survey data from Georgia, Mongolia, and the Philippines, we examine gender gaps in entrepreneurship. The overall incidence of entrepreneurship is highest in Cavite, Philippines, while the gender gap in ownership is highest in Mongolia. On average, enterprises operated by men have larger firm size relative to those operated by women. Except for Mongolia, the average income of male-owned enterprises is greater than the average income of female-owned enterprises. Multivariate analysis suggests that the determinants of income vary by gender and across countries. Using the Oaxaca-Blinder decomposition, we find the average difference in income between men's and women's enterprise is not significant in Mongolia. More than 50% of the gender income gap is explained by observable characteristics in Georgia and the Philippines. On average, the income of female-owned enterprises would have seen a rise of 64% (Cavite, Philippines) and 59% (Georgia) if they had the same characteristics as male-owned firms.
Keywords: J16; L26; O31; 330; Georgia; Mongolia; Philippines; entrepreneurship; nonagricultural enterprises; gender-income gap